Efficiency and Predictive Power of Technical Trading Rules in Post-COVID-19 Era : A Study of BRICS Stock Market - Poonam,; Malik, N. S. (Indian Journal of Finance, 2025)
Purpose : This study was an attempt to test the efficiency and revalidate the technical trading strategies based on the exponential moving average (EMA), relative strength index (RSI), and moving average convergence divergence (MACD) on stock returns in Brazil, Russia, India, China, and South Africa (BRICS) before and after the COVID-19 pandemic. Methodology : The stock markets of BRICS were used from January 1, 2016, to February 29, 2024, to test the effectiveness of EMA, RSI, and MACD in a pre- and post-COVID sample. Findings : The study did not suggest using EMA, RSI, and MACD indicators to generate buy and sell for a day trader because the technical rules under consideration failed to generate a positive alpha ratio ; hence, EMA, RSI, and MACD emerged as the low-performing technical trading rules for generating better stock returns than the â€œbuy-holdâ€ strategy in the BRICS stock market. Practical Implications : Investors or traders in the stock markets of BRICS countries could clearly understand whether to use or not use the technical trading strategies studied in this research. Originality : Unlike prior research on technical analysis, the current work provided a systemic way of back-testing technical trading strategies like EMA, RSI, and MACD.